Psychoanalysis and the Phenomenon of Leadership (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
ABSTRACTThe article examines leadership through the lens of Psychoanalysis, emphasizing how Freudian concepts such as transference, identification, projection, and idealization manifest in leader–follower relationships. The author explores unconscious dynamics within organizational power structures and proposes leadership as an affective and symbolic practice. The psychoanalytic approach is shown to expand understanding of organizational behavior and promote more ethical and empathic management.
Keywords: Psychoanalysis; Leadership; Unconscious; Transference; Identification.